2016
DOI: 10.1016/s1525-0016(16)33457-8
|View full text |Cite
|
Sign up to set email alerts
|

649. Developing FGFR4 Chimeric Antigen Receptor CAR T Cell Therapy Against Rhabdomyosarcoma

Abstract: Figure 1. CD4CARNK cells kill both peripheral T cell lymphoma cell line and primary patient malignant cells at effector to target ratios of 2 to 1 and 5 to 1. Peripheral T cell lymphoma cell lines and primary patient T cell leukemia lymphoma samples were co-cultured for 24 hours with CD4CAR NK cells. The percent of malignant cell killing was determined by comparison to vector control transduced NK cells via flow cytometry analysis of cell survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In particular, T cells genetically modified to express a CAR that targets FGFR4 have been developed for treatment of RMS tumors [ 151 ]. Testing of these FGFR4-specific CAR T cells in vitro and in mouse models revealed promising effects of these T cells in killing tumor cells and suggested that these agents could be beneficial for treatment of high-risk, refractory and relapsed RMS [ 126 , 127 , 163 ]. In addition, IGFR1-specific CAR T cells were recently developed, and initial results indicated that they suppress growth of several sarcoma categories expressing this receptor in both cell line and xenograft systems [ 164 ].…”
Section: Immunotherapy Applications To Target Pax3-foxo1 and Downsmentioning
confidence: 99%
“…In particular, T cells genetically modified to express a CAR that targets FGFR4 have been developed for treatment of RMS tumors [ 151 ]. Testing of these FGFR4-specific CAR T cells in vitro and in mouse models revealed promising effects of these T cells in killing tumor cells and suggested that these agents could be beneficial for treatment of high-risk, refractory and relapsed RMS [ 126 , 127 , 163 ]. In addition, IGFR1-specific CAR T cells were recently developed, and initial results indicated that they suppress growth of several sarcoma categories expressing this receptor in both cell line and xenograft systems [ 164 ].…”
Section: Immunotherapy Applications To Target Pax3-foxo1 and Downsmentioning
confidence: 99%
“…Moreover, we could achieve effective cell-mediated cytotoxicity with FGFR4-CAR T cells in vitro. Therapies for RMS based on FGFR4 antibodies have been investigated pre-clinically with promising results, either as antibody–drug conjugates (ADC) [ 56 , 57 , 58 ], or with the antigen-binding domain grafted on chimeric antigen receptors (CARs) to generate CAR T cells [ 59 ]. With our work, we show here a novel FGFR4-targeting based on sdAb by active drug delivery and T cell recruitment.…”
Section: Resultsmentioning
confidence: 99%
“…FGFR4 inhibition was effective in preclinical studies of FN-RMS and FP-RMS and FGFR4 is differentially expressed in RMS compared to mature skeletal muscle, therefore it may be a beneficial target for immunotherapy [ 109 , 110 ]. FGFR4 targeted chimeric antigen receptor (CAR) T-cells are currently in pre-clinical development and were effective against RMS in both in vitro and in vivo studies [ 111 , 112 , 113 ].…”
Section: Other Targeted Agentsmentioning
confidence: 99%